Filling Gaps in the Lexicon of the Literary Language with Colloquial Words - Abdumannon Majidovich Khasanov (Researchparks Publishing, 2022)
In this article, proposals and recommendations on the use of words specific to colloquialisms have been developed to fill the lexicon of the literary language. Norms and criteria for the acceptance of colloquial words into the lexicon of the literary language have been developed. Methods of identifying gaps in the lexicon of the literary language are described. Considerations for filling them were studied on the example of the Uzbek language, and it was emphasized that the available opportunities should be used effectively. In the development of each language by people and nations, the important aspects of conversational speech are shown. It is proved that the units formed as a result of filling the gaps in the language lexicon in speech situations are stabilized in the lexicon of the literary language.